Effects of repetitive transcranial magnetic stimulation in subjects with sleep disorders - Nardone, Raffaele; Sebastianelli, Luca; Versace, Viviana; Brigo, Francesco; Golaszewski, Stefan; Pucks-Faes, Elke; Saltuari, Leopold; Trinka, Eugen (Sleep medicine, 2020)
In this review, we aimed at identifying the studies that have employed repetitive transcranial magnetic stimulation (rTMS) in patients with sleep disorders. Low-frequency (LF) rTMS stimulating the right dorsolateral prefrontal cortex (DLPFC) or the posterior parietal cortex (PPC) was found to be effective to reduce cortical hyperexcitability and improve the sleep quality in subjects with chronic primary insomnia (PI). Both high-frequency (HF) and LF rTMS applied over the primary motor cortex or the supplementary motor cortex seem to have transient beneficial effects in patients with restless legs syndrome (RLS). Stimulation of upper airway muscles during sleep by isolated TMS and by rTMS twitch can improve airflow dynamics in obstructive sleep apnea syndrome (OSAS) patients without arousal. A single case report study indicates that HF rTMS over the left DLPFC might represent an alternative choice for symptom control in narcoleptic patients with cataplexy, and a pilot study also raises the possibility of therapeutic benefits from rTMS in patients with sleep bruxism. rTMS may also exert intrinsic effects on hypersomnia in depressed adolescents. In conclusion, rTMS may contribute to the development of new non-pharmacological therapeutic options for several sleep disorders. rTMS might be useful as therapeutical tool in particular in patients with PI, RLS, OSAS and narcolepsy, while its effect in other sleep disorders (ie, parasomnias) has not yet been explored. rTMS integrated with clinical, sleep-related, and neuroimaging data may represent an effective tool in modulating cortical excitability and inducing short-term synaptic plasticity. Further studies with larger patient samples, repeated sessions, an optimized rTMS setup, and clinical follow-up warranted to verify the initial findings, and to expand clinical and research interest towards neuromodulation in the different sleep disorders. •LF rTMS over DLPFC or PPC was effective to improve sleep quality in subjects with PI.•HF and LF rTMS over M1 or SMA has beneficial effects in patients with RLS.•rTMS of upper airway muscles can improve airflow dynamics in OSAS.•HF rTMS over DLPFC might improve EDS symptoms and cataplexy in narcoleptic patients.•rTMS may exert therapeutic benefits in patients with sleep bruxism.